New Zealand Inventory of Biodiversity - Gregory, Geoff (New Zealand Science Review, 2016)
​New Zealand was the first country to catalogue its entire living and fossil biodiversity, with the release from Canter- bury University Press of the third and final part of New Zealand Inventory of Biodiversity in 2012. The whole inventory was edited by NIWA biodiversity scientist Dr Dennis Gordon, and was the culmination of an international effort he led involving 237 other authors from New Zealand and overseas. It offers the first review of New Zealand’s entire complement of known species of animals, plants, fungi and micro-organisms – some 56,000-plus living and 14,000-plus fossil species – and covers all life in all environments, from the Cambrian to the present day, including both native and naturalised alien species.